Model Kelembagaan pada Agribisnis Padi Organik Kabupaten Tasikmalaya - Nuraini, Candra; Darwanto, Dwidjono Hadi; Masyhuri, Masyhuri; Jamhari, Jamhari (Universitas Muhammadiyah Yogyakarta, 2016)
This study aims to: (1) to identify the forms of institutional and analyze interaction at the institutional organic rice agribusiness; (2) to design the institutional model in organic rice agribusiness. The study was conducted by using descriptive method. Result of the analysis showed that the profile of organic rice agribusiness institutions include: farmers, farmers' groups combined Sympathy, organic farmers cooperatives, village cooperatives, private enterprises agro-industry (CV), BPP, NGO, exporters, agro-industry company. The conditions of farmer organizations today are more cultural and mostly just to government facilities, it has not been fully geared to take advantage of economic opportunities through the use of accessibility to information technology, capital and markets necessary for the development of organic rice agribusiness and agricultural businesses.On the other hand, institutional businesses in rural areas, such as the cooperative has not fully accommodate the interests of farmers / farmer groups as a forum for technical guidance. Various farmer institution that already exist such as farmers 'groups, farmers' groups combined, the association of water user farmers are expected on the challenges ahead to revitalize themselves and institutions that currently more dominant just as container technical development and social into institutional also serve as a platform for business development legal entity or can integrate other institutions in the agribusiness chain of organic rice. Model on organic rice agribusiness institution system is based on agribusiness and institutional dimensions as well as the three pillars of the new institutional.